2017
DOI: 10.1063/1.4995985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface dielectric barrier discharge on aerodynamic characteristic of train

Abstract: High-speed railway today has become an indispensable means of transportation due to its remarkable advantages, including comfortability, convenience and less pollution. The increase in velocity makes the air drag become the main source of energy consumption, leading to receiving more and more concerns. The surface dielectric barrier discharge has shown some unique characteristics in terms of active airflow control. In this paper, the influences of surface dielectric barrier discharge on the aerodynamic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A Q-V Lissajous diagram was obtained by voltages on electrodes 1 and 2. The mechanism of Q-V Lissajous and power calculation has been described. , The voltage and current signals were collected by a digital oscilloscope (DPO3012, Tektronix, Inc.). The emission spectrum from SDBD was collected by a collimating lens (focal length: 10 mm) and analyzed by a spectrometer (Maya2000PRO, Ocean Optics).…”
Section: Methodsmentioning
confidence: 99%
“…A Q-V Lissajous diagram was obtained by voltages on electrodes 1 and 2. The mechanism of Q-V Lissajous and power calculation has been described. , The voltage and current signals were collected by a digital oscilloscope (DPO3012, Tektronix, Inc.). The emission spectrum from SDBD was collected by a collimating lens (focal length: 10 mm) and analyzed by a spectrometer (Maya2000PRO, Ocean Optics).…”
Section: Methodsmentioning
confidence: 99%
“…The body force can induce a wall jet in quiescent air, and in an existing flow the body force is employed to get a beneficial modification of the mean velocity profile of the near-wall flow [9]. Dong et al [10] proposed that the drag reduction of a scaled train model can be obtained by using a SDBD plasma actuator to suppress the flow separation. They also found that the surface temperature of the dielectric and the induced flow velocity were increased as the applied voltage increased.…”
Section: Introductionmentioning
confidence: 99%